Stabilizing p‐Dithiobenzyl Urethane Linkers without Rate‐Limiting Self‐Immolation for Traceless Drug Release. (16th May 2019) - Zheng, Yiwu; Shen, Yang; Meng, Xiaoting; Wu, Yaqi; Zhao, Yibing; Wu, Chuanliu
Abstract: Exploiting the redox sensitivity of disulfide bonds is a prevalent strategy in targeted prodrug designs. In contrast to aliphatic disulfides, p ‐thiobenzyl‐based disulfides have rarely been used for prodrug designs, given their intrinsic instability caused by the low p K a of aromatic thiols. Here, we examined the interplay between steric hindrance and the low‐p K a effect on thiol–disulfide exchange reactions and uncovered a new thiol–disulfide exchange process for the self‐immolation of p ‐thiobenzyl‐based disulfides. We observed a central leaving group shifting effect in the α, α‐dimethyl‐substituted p ‐dithiobenzyl urethane linkers (DMTB linkers), which leads to increased disulfide stability by more than two orders of magnitude, an extent that is significantly greater than that observed with typical aliphatic disulfides. In particular, the DMTB linkers display not only high stability, but also rapid self‐immolation kinetics due to the low p K a of the aromatic thiol, which can be used as a general and robust linkage between targeting reagents and cytotoxic drugs for targeted prodrug designs. The unique and promising stability characteristics of the present DMTB linker will likely inspire the development of novel targeted prodrugs to achieve traceless release of drugs into cells. Abstract : Leave no trace : We examined the effect of two methyl groups adjacent to p ‐thiobenzyl‐based disulfides on thiol–disulfide exchange reactions and elucidated the mechanism behind the reduction and self‐immolation of these disulfides. A central leaving group shifting effect in these p ‐thiobenzyl‐based disulfide linkers leads to increased disulfide stability by more than two orders of magnitude. This work provides useful self‐immolating disulfide linkers for targeted cytotoxic prodrug designs.